2010
DOI: 10.1002/jbm.b.31695
|View full text |Cite
|
Sign up to set email alerts
|

Novel three‐dimensional scaffolds of poly(L‐lactic acid) microfibers using electrospinning and mechanical expansion: Fabrication and bone regeneration

Abstract: Poly(L-lactic acid) (PLLA) microfibrous scaffolds with three-dimensional (3D) structures were fabricated using an electrospinning technique with a subsequent mechanical expansion process. To achieve a 3D fibrous structure, the fusion at the contact points of the as-spun PLLA microfibers was avoided using an appropriate binary solvent system of methylene chloride and acetone. The solvent composition was optimized based on the solvent power, volatility, and viscosity (methylene chloride:acetone = 9:1 volume rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 30 publications
(31 reference statements)
0
52
0
2
Order By: Relevance
“…The differentiation-promoting effects of three-dimensional growth of osteoblast (-like) cells induced by the presence of artificial 3D scaffolds have been demonstrated by others. [18][19][20] Since proper osteogenesis requires a delicate balance between proliferation and differentiation, further studies are needed to analyze the influence of our scaffolds on hallmarks of osteoblast differentiation, such as alkaline phosphatase activity, osteocalcin secretion, or hydroxyapatite deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation-promoting effects of three-dimensional growth of osteoblast (-like) cells induced by the presence of artificial 3D scaffolds have been demonstrated by others. [18][19][20] Since proper osteogenesis requires a delicate balance between proliferation and differentiation, further studies are needed to analyze the influence of our scaffolds on hallmarks of osteoblast differentiation, such as alkaline phosphatase activity, osteocalcin secretion, or hydroxyapatite deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Then, PLLA is modified or copolymerized with other degradable polymers to reduce degradation time, as shown by the use of radiations to create radicals in the ester alpha carbon which, upon rearrangement, shortens the polymer backbone through the removal of an ester bond and the release of carbon dioxide [100,101]. PLLA is used as bone fixator, scaffold for bone [102,103], cartilage [104], tendon [105], neural [106], and vascular [107] regeneration. Similarly, PDLLA is an amorphous polymer with the random positions of its two isomeric monomers within the polymer chain.…”
Section: Polyestersmentioning
confidence: 99%
“…Shim et al showed it is possible to modify sheets of nanofibers post-production to expand them into three dimensions. 130 Specifically, this group used a small metal comb to pull the nanofibers apart to decrease the overall nanofiber density and increase porosity of the PLLA scaffolds. Blakeney et al approached the dimensionality issue by modifying the nanofiber collector, altering the structure of a PCL nanofiber scaffold as the nanofibers were deposited.…”
Section: Other Aspects Of Drug-loaded Electrospun Nanofibersmentioning
confidence: 99%